Mutagenesis of the murine cytomegalovirus M56 terminase gene - Wang, Jian Ben (2008)
The M56 gene encodes M56, one of three proteins comprising the murine cytomegalovirus (MCMV) terminase, an enzyme that packages DNA into capsids and cleaves the DNA into progeny genomes. Deletion of M56 from a bacterial artificial chromosome (BAC) clone of the MCMV genome was lethal, as the mutant BAC failed to reconstitute infectious virus. Reintroduction of M56 at an ectopic locus complemented the deletion, allowing reconstitution of a virus that replicated with wild type efficiency. Reintroduction of M56 sequences encoding an N-terminal epitope fusion was lethal, as was a mutation targeting a region in M56 implicated as an ATPase active site. In contrast, a frame shift mutation in M56a, an open reading frame that overlaps M56, had no effect on viral replication. We conclude that the protein product of M56a is dispensable while M56 residues comprising the proposed ATPase active site are critical for terminase function and viral replication.